PERFORMANCE OF STRING BEANS AS AFFECTED BY DIFFERENT LEVELS OF CHICKEN MANURE TEA - TARUMA, ARVIN BUEMIA; BALINQUIT, MARY GRACE BROSO (International Journal of Multidisciplinary Research and Studies, 2022)
This study was conducted to look for alternative measures to sustain the profitability of cultivating string beans by using different levels of chicken manure tea. An Experimental Research in Randomized Complete Block Design (RCBD) was used in this study of different levels of chicken manure tea as treatment. The treatments used were as follows: Control (T1), Chicken manure tea at 25%: 75% water dilution (T2), Chicken manure tea at 50%: 50% water dilution (T3), and Pure chicken manure tea (T4). The results show that growth characteristics such as the number of days from sowing to flowering, to fruiting, to harvesting, plant height, and yield components including the diameter of pods, the weight of pods per harvest area, and computed yield per hectare did not show significant difference among treatment means and not affected by different levels of chicken manure tea as fertilizer materials. However, the length of pods was affected by different levels of chicken manure tea as a treatment used in the study. It can be concluded that different levels of chicken manure tea as fertilizer materials does not significantly affect the growth and yield of string bean. However, the concentration of pure chicken manure tea (T4) increased the production and net income of string beans, and replication of the study is recommended and the use of other crops may also be considered in this study.